Correction of periodic displacement non-linearities by two-wavelength interferometry - associated data - Bridges, Angus; Yacoot, Andrew; Kissinger, Thomas; Humphreys, David A.; Tatam, Ralph P. (Cranfield University, 2021)
Data associated with the publication "Correction of periodic displacement non-linearities by two-wavelength interferometry".
Keywords: Interferometry'; 'Non-linearity'; 'Dimensional Metrology'; 'Applied Physics'; 'Optical Physics not elsewhere classified'